EFEKTIVITAS MEDIASI OLEH TOKOH AGAMA SEBAGAI MEDIATOR DALAM SYIQAQ (Studi Kasus Desa Sumbermulyo Kecamatan Jogoroto Kabupaten Jombang) - Mohammad Brilyan Aqil Alkhowarizmi; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The role of religious figures as mediators can be an alternative way for the parties to help reconcile the problem. Choosing a religious figure as a mediator is a dispute resolution step to avoid lawsuits in court. By using a spiritual approach, religious leaders are able to straighten out things that are still lacking in the household foundation, as well as apply the concept of rights that do not exist in mediation in court. The aim of this research is to determine the effectiveness of mediation by religious figures as mediators in Shiqaq cases in Sumbermulyo Village, Jogoroto District, Jombang Regency. Qualitative methods, as well as observing research objects and interviewing parties, are the methods that will be used in this research. Based on research data, the overall percentage of effectiveness of mediation by religious leaders in Sumbermulyo Village in 2021-2023 reached 63%